Effects of surface optical and radiative properties on the thermal performance of a solar cavity receiver. (1st September 2018) - Fang, Jiabin; Tu, Nan; Wei, Jinjia; Du, Xuancheng
Highlights: An integrated method based on a two-band semi-gray surface approximation is employed. The solar absorptivity is a critical parameter relative to other surface properties. The receiver efficiency shows different variations with the thermal emissivity. The infrared heat transfer direction between passive and active surfaces is crucial. The passive surfaces should be highly reflective due to the great cavity effect. Abstract: Solar cavity receiver is one of the most crucial components in a solar power tower system, where the solar-thermal conversion process is achieved. Optimizing the surface properties (viz. absorptivity and emissivity) of a designed cavity receiver is a viable option to improve its thermal efficiency. In the present paper, an integrated simulation approach was employed to quantify the influence of surface optical and radiative properties on the thermal performance of a typical water/steam solar cavity receiver. Firstly, the different candidate surface materials, solar selective and non-coated, were compared. The results showed that the thermal efficiency of the receiver with the ideal coating and Pyromark 2500 is respectively enhanced by 12.5% and 7.8% compared with that of the non-coated receiver. And then, the effects of surface spectral selectivity on the thermal performance of the receiver were carefully analyzed. It can be found that the solar absorptivity is the most critical parameter for improving the receiver efficiency, which is enhanced by about 12.6% as the solar absorptivity rises from 0.8 to 1.0. However, the receiver efficiency shows different variation tendencies with the thermal emissivity of active surfaces, which are closely related to the infrared heat transfer direction between the passive surfaces and the active surfaces. Furthermore, with the increase of reflectivity of passive surfaces over the full spectrum, the receiver efficiency is determined by a trade-off between the increasing reflective heat loss and the decreasing radiative and convective heat losses. For the present receiver, the thermal efficiency is improved by about 4.8% with the reflectivity increasing from 0 to 1.0 due to its great cavity effect. Therefore, the passive surfaces should be highly reflective throughout the spectrum inside the present receiver.